The Pathogens of Catheter Related Bloodstream Infections in the Intensive Care Unit of Keçiören Training and Research Hospital in 2018 - Leyla Ipek Rudvan Al (Ankara Medical Journal, 2020)
INTRODUCTION: Intravenous catheters are frequently used in today's medical practice and are inevitable in some cases, especially in intensive care units. Due to these common areas of use, they are associated with increased morbidity and mortality due to the complications they cause. One of these complications is infectious complications, the most important of which is catheter-related bloodstream infection (CRBI). In this study, we aimed to reveal the factors of catheter-related bloodstream infection that we diagnosed in the intensive care unit of our hospital. METHODS: In order to determine the factors and antibiotic susceptibility catheter-related bloodstream infections which were the subjects of our study, who had been hospitalized between January 2018 and December 2018 at Keçiören Training and Research Hospital Intensive Care Unit and concurrent in catheter blood culture and peripheral blood.216 patients who were cultured were evaluated retrospectively. RESULTS: In 20.3% of the patients, catheter-related bloodstream infection was detected, in which 6 of these cases were E. faecium, 6 of them were K. pneumonia, 6 of them were A. baumanii, and 6 of them were S. epidermidis. In 4 patients we detected S. capitis and E. faecalis. S. aureus-P.aeroginosa-S.haemolyticus-C. albicans and E.coli were isolated in both 2 patients. In our study, E. faecium, S. epidermidis, A. baumanii and K. pneumoniae were the most common agents, while the second most frequent agents were S. capitis and E faecalis. When we evaluate our study, coagulase-negative staphylococci are in the first place as the cause of CRBI and enterococci are in the second place. DISCUSSION AND CONCLUSION: The distribution results of the causes of CRBI of our hospital's intensive care unit was compatible with Turkey's national nosocomial infections surveillance system-2012.